Serum Antibody Profile of a Patient With Coronavirus Disease 2019 Reinfection. (23rd September 2020) - To, Kelvin Kai-Wang; Hung, Ivan Fan-Ngai; Chan, Kwok-Hung; Yuan, Shuofeng; To, Wing-Kin; Tsang, Dominic Ngai-Chong; Cheng, Vincent Chi-Chung; Chen, Zhiwei; Kok, Kin-Hang; Yuen, Kwok-Yung
Abstract: We recently reported a patient with coronavirus disease 2019 reinfection. Here, we show that serum neutralizing antibodies could be detected during the first episode but not at the presentation of the second episode. During reinfection, neutralizing antibodies and high avidity immunoglobulin G were found within 8 days after hospitalization, whereas immunoglobulin M response was absent.